The Relationship of HBA1C with Mean Platelet Volume (MPV) in Type 2 Diabetes Mellitus Patients - Muhammad Sahid; Dewi Saroh (GLOBAL HEALTH SCIENCE GROUP, 2023)
Diabetes Mellitus (DM) is a chronic disease that occurs due to the failure of the pancreas to produce sufficient insulin. Diabetes Mellitus not only causes death but is also a major cause of blindness, heart disease, and kidney failure. Examination of HbA1c levels in the blood serves to help diagnose diabetes mellitus. A high HbA1c value is used as a measure of the development of diabetes complications. Mean Platelet Volume (MPV) is a marker of platelet function and activation. Platelets in DM patients will synthesize thromboxane in larger quantities than normal platelets. So it is important to check Hba1c and MPV to detect complications. This study aims to determine the relationship between HbA1c and MPV values ​​in type-2 DM patients. The type of research used is observational analysis with a cross-sectional approach. The sampling technique was quota sampling technique, then the results were analyzed using the Spearman correlation test. The results of the Spearman's Rho correlation test in this study showed a significant p-value of 0.100, which means that there is no significant relationship between HbA1c levels and MPV values ​​in patients with type 2 DM.